Islamic Education During the Abbasid Dynasty and the Development of Modern Islamic Education - Siti Soleha; Lina Pusvisasari (Penerbit Hellow Pustaka, 2024)
Education is a teaching and learning process that involves interaction with the surrounding environment. Islamic educational institutions strive to increase students' faith, understanding, appreciation and experience of the Islamic religion, so that they become individuals who believe and are devout in their personal, social, national and state lives. Islamic education has developed since the time of Rasulullah SAW., Khulafaur Rashidin, Bani Umayyah, Bani Abbasiyah, and continues to develop until now. The progress of Islamic education was especially visible during the Abbasid dynasty. This article aims to discuss the concept of Islamic education during the Abbasid Dynasty and the development of modern Islam. The research method used is descriptive qualitative, with sources of information from various print and online media regarding this topic. The research results show that Islamic educational institutions during the Abbasid Dynasty can be categorized into three types. First, informal educational institutions such as the ulama's homes. Second, non-formal educational institutions such as kutabs, mosques, bookstores and libraries. Third, formal educational institutions such as madrasas. The many types of educational institutions are in accordance with Islamic teachings which require studying as a form of worship, so that places of study are not limited to just one location.